Formation of trihalomethanes and haloacetic acids from 2, 6-dichloro-1, 4-benzoquinone during chlorination: Decomposition kinetics, conversion rates, and pathways. (March 2022) - Zhai, Hongyan; Zhao, Jun; Wang, Rumeng; Yan, Yuwei; Yu, Shanshan; Zhao, Yingxin
Abstract: As a typical aromatic disinfection byproduct (DBP), 2, 6-dichloro-1, 4-benzoquinone (2, 6-DCBQ) attracts much concern due to the potential toxicity. To further evaluate the role of 2, 6-DCBQ as an intermediate DBP in water with or without chlorine, their decomposition characteristics and transformation potential to the regulated DBPs (i.e., trihalomethanes (THMs) and haloacetic acids (HAAs)) were investigated under different chlorine doses, pH values, temperatures, contact times, and bromide levels. The decomposition of 2, 6-DCBQ under different conditions all fit apparent first-order kinetics. The hydrolysis rate constants of 2, 6-DCBQ significantly increased with pH. The half-live values of 2, 6-DCBQ were 108.3–568.7 h at pH 6.0–6.5, and 1.8–31.1 h at pH 7.0–8.5. During the hydrolysis of 2, 6-DCBQ, there was no THMs and HAAs generated. During chlorination, 2, 6-DCBQ decayed rapidly accompanied by the fast formation of trichloromethane (TCM) and the gradual generation of dichloroacetic acid and trichloroacetic acid. The molar conversion rates of 2, 6-DCBQ-to-THMs (i.e., TCM) and 2, 6-DCBQ-to-HAAs were 2.9–10.0% and 0.1–2.2% under different conditions. The presence of bromide increased the conversion rates of 2, 6-DCBQ-to-THMs and caused the generation of brominated THMs and HAAs. According to the decomposition characteristics of 2, 6-DCBQ and the formation trends of THMs and HAAs under different conditions, multiple formation pathways from 2, 6-DCBQ to THMs and HAAs were proposed. Graphical abstract: Image 1 Highlights: The half-live values of 2, 6-DCBQ were 108.3–1732.9 h in water at pH 6.0–8.5 Conversion rates 2, 6-DCBQ to THMs and HAAs were 2.9–10.0% and 0.1–2.2%. Bromide increased the formation of Br-DBPs and the conversion of 2, 6-DCBQ to DBPs. Multiple formation pathways from 2, 6-DCBQ to THMs and HAAs were proposed.